WAPL orchestrates porcine oocyte meiotic progression via control of spindle assembly checkpoint activity - Changyin Zhou; Yilong Miao; Xue Zhang; Bo Xiong (BMC, 2021)
Abstract Background In mitotic cells, WAPL acts as a cohesin release factor to remove cohesin complexes from chromosome arms during prophase to allow the accurate chromosome segregation in anaphase. However, we have recently documented that Wapl exerts a unique meiotic function in the spindle assembly checkpoint (SAC) control through maintaining Bub3 stability during mouse oocyte meiosis I. Whether this noncanonical function is conserved among species is still unknown. Methods We applied RNAi-based gene silencing approach to deplete WAPL in porcine oocytes, validating the conserved roles of WAPL in the regulation of SAC activity during mammalian oocyte maturation. We also employed immunostaining, immunoblotting and image quantification analyses to test the WAPL depletion on the meiotic progression, spindle assembly, chromosome alignment and dynamics of SAC protein in porcine oocytes. Results We showed that depletion of WAPL resulted in the accelerated meiotic progression by displaying the precocious polar body extrusion and compromised spindle assembly and chromosome alignment. Notably, we observed that the protein level of BUB3 was substantially reduced in WAPL-depleted oocytes, especially at kinetochores. Conclusions Collectively, our data demonstrate that WAPL participates in the porcine oocyte meiotic progression through maintenance of BUB3 protein levels and SAC activity. This meiotic function of WAPL in oocytes is highly conserved between pigs and mice.